Growth Response and Production of Broccoli (Brassica oleracea) With Application of Azolla Composting at Several Plant Spacing - Barus, Wan Arfiani; Khair, Hadriman; Irawan, Muhammad Fatrian (Talenta Publisher, 2018)
This study aims to determine the growth response and Plant Production of Broccoli (Brassica oleracea Var. Botrytis) with application of Azolla composting in some plant spacing. This research used a Factorial Randomized Block Design with two factors namely: Azolla Composting Factor (A) with 4 levels 0, 32, 64, 96 and A4 = 128 g/plant. Plant spacing factor with 3 levels 45 cm x 45 cm, 50 cm x 50 cm and 55 cm x 55. The results showed that the application of Azolla compost 128 g/plant had significant effect on the stem height, stem diameter and flower weight. Plant spacing in 55 cm x 55 cm only affected the flower weight. There was no interaction between Azolla compost and plant spacing for all parameter observed.